If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(6x + -9) = -34 Reorder the terms: 0.6(-9 + 6x) = -34 (-9 * 0.6 + 6x * 0.6) = -34 (-5.4 + 3.6x) = -34 Solving -5.4 + 3.6x = -34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5.4' to each side of the equation. -5.4 + 5.4 + 3.6x = -34 + 5.4 Combine like terms: -5.4 + 5.4 = 0.0 0.0 + 3.6x = -34 + 5.4 3.6x = -34 + 5.4 Combine like terms: -34 + 5.4 = -28.6 3.6x = -28.6 Divide each side by '3.6'. x = -7.944444444 Simplifying x = -7.944444444
| 3(4)-2(5(4)+3)=14-2(4) | | 0.6x+9=-34 | | 7(-4+x)=-84 | | 8(g-5)=8 | | 4(1)-3y=1 | | 3(2x+8)+2x=56 | | z^2-2z+26=0 | | 15x-7=40 | | =75+(15+8)w | | 16=-2x+4 | | 6m+3=0 | | b=75+(15+8)w | | z-7=11 | | 25x+13=63 | | 4(0)-3y=1 | | x-75=100 | | -4h-2-5h=21 | | 9x-2+8x-4+7x-6=180 | | 2(6)+25=300 | | 14x^2+12x-3=0 | | 18-y=y | | 45=2(c+12) | | -4.64a=31.552 | | 9X-2X-3=5X+2 | | 115=5x+15 | | 2ln(x)=ln(7x) | | 8w-4=20 | | -5x-2x+3=0 | | 4x-(12)=60 | | 46=(c+11) | | 43.52=9g+3.56 | | 2ln(x)=ln(7) |